2017
DOI: 10.1177/0004867417728806
|View full text |Cite
|
Sign up to set email alerts
|

Treating body, treating mind: The experiences of people with psychotic disorders and their general practitioners – Findings from the Australian National Survey of High Impact Psychosis

Abstract: People with psychotic disorders consult general practitioners, some very frequently. Most Australian general practitioners believe they have a responsibility to review the physical and mental health of their patients. Improved communication between general practitioners and mental health services, and easier access to mental health support, may help general practitioners manage the complex mental, physical and social problems of their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
4
14
1
Order By: Relevance
“…In contrast, no significant associations were observed for attendance at ED or outpatient services, or for home visits, when adjusting for potential confounders. These findings add to previous evidence linking loneliness in psychosis to increased use of somethough not allforms of health care services (Chrostek et al, 2016;Waterreus and Morgan, 2018). However, these previous studies showed these relationships, with either no adjustment, or adjusting for a more limited range of confounding factors.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In contrast, no significant associations were observed for attendance at ED or outpatient services, or for home visits, when adjusting for potential confounders. These findings add to previous evidence linking loneliness in psychosis to increased use of somethough not allforms of health care services (Chrostek et al, 2016;Waterreus and Morgan, 2018). However, these previous studies showed these relationships, with either no adjustment, or adjusting for a more limited range of confounding factors.…”
Section: Discussionsupporting
confidence: 74%
“…For example, recent eWSSASvidence suggests that people who feel lonely and lacking social connectedness visit their general practitioners (GP) more often than those who are not lonely (Cruwys et al, 2018; see also Ellaway et al, 1999). A similar pattern of results has also been reported in people with psychotic disorders (Waterreus and Morgan, 2018). In fact, annual use of GP services by people with psychotic disorders has increased over the last decade, reflecting a shift from in-patient to community-based care (Raudino et al, 2014).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Unit costs for consultations were obtained from national estimates of the cost per minute of general practitioner (GP) and practice nurse time for 2014 [29]. We used visit duration data rather than a standard visit cost because of evidence suggesting that consultations for patients with mental health problems are longer than average [30][31][32][33]. We considered multiple visits in a day for a patient to a single staff member as duplicates, but allowed for visits to different staff members on the same day.…”
Section: Primary Care Costsmentioning
confidence: 99%
“…133 We used individual visit duration data to calculate visit costs rather than a standard unit cost because of evidence suggesting that consultations for patients with mental health problems are likely to be longer than average consultations. [137][138][139][140] We considered multiple visits in a day for a patient to a single staff member as duplicates, but included visits to different staff members on the same day.…”
Section: Samplementioning
confidence: 99%